Power Quality on Wind Turbine Energy Output - Uslu, Ahmet Furkan; Dogansahin, Kadir; Kekezoglu, Bedri (IEEE, 2018)
The share of wind energy in electric energy generation increase day by day. The penetration of wind power plant in power systems has come to considerable size. On the other hand, power quality concerns are on rise. In this study, the data obtained by measurements of power quality parameters performed on a real power system are studied. The data are evaluated by the available legislations related on power quality
Keywords: wind power plants; power quality; harmonics; voltage; Automation & Control Systems; Computer Science; Engineering